The problems of market regulations in the modern world - A. A. Soldatov (Дискурс)
Introduction. The mechanisms influence of the political processes on the world economics and the role of the states as the components of the political order in these processes are analyzed. Is there any irresistible antagonism between such notions as «market» and «state»?Materials and methods. The sociological analysis of the processes in the market formation in the context of the great representative’s works of the modern sociological and economical thought such as F. Blok, J. Coleman, N. Fligstein, K. Polany, Ch. Mills, I. Vallerstein is used.Results. The factor of the negative state influence on the regulation of the economical processes is rather often indicated in the Russian and foreign scientific practice. But the sociological analysis in this work shows that there is a great number of ways in the positive participation of the state structures in the formation of the social institutes including markets.Discussion. Under the definition accepted in modern sociology" subject of economic activity" includes both individuals, and large economic entities. They can be both physical and legal persons including the State. From the point of view of the classical sociological approach the State in relation to the economy always acts as an external force and its role is reduced mainly to the creation of favorable conditions for business which is nothing but interference in economic life.Conclusion. Consequently, in the structure of the modern capitalist world there is no insuperable antagonism between such concepts as the market and the State, in the process of forming a new world order they as the most important political institutions closely interact with each other and exert corresponding influence on each other.